2016
DOI: 10.1113/jp273200
|View full text |Cite
|
Sign up to set email alerts
|

Human motoneurone excitability is depressed by activation of serotonin 1A receptors with buspirone

Abstract: Intense serotonergic drive in the turtle spinal cord results in serotonin spillover to the axon initial segment of the motoneurones where it activates serotonin 1A (5-HT ) receptors and inhibits generation of action potentials. We examined whether activation of 5-HT receptors decreases motoneurone excitability in humans by determining the effects of a 5-HT receptor partial agonist, buspirone, on F waves and cervicomedullary motor evoked potentials (CMEPs). In a placebo-controlled double-blind study, 10 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…Ingestion of the 5‐HT1 A agonist, buspirone, induces clear reductions in motoneurone excitability (D'Amico et al . ), which limits the capacity to perform prolonged bouts of exercise (Marvin et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ingestion of the 5‐HT1 A agonist, buspirone, induces clear reductions in motoneurone excitability (D'Amico et al . ), which limits the capacity to perform prolonged bouts of exercise (Marvin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Although 5-HT mechanisms that reduce motoneurone excitability have been identified for the turtle spinal cord, the inhibitory effect that 5-HT 1A receptors have on motor function has also been confirmed in humans. Ingestion of the 5-HT1 A agonist, buspirone, induces clear reductions in motoneurone excitability (D'Amico et al 2017), which limits the capacity to perform prolonged bouts of exercise (Marvin et al 1997). It should be noted, however, that exogenous activation of the 5-HT 1A receptor may cause different responses to endogenously released 5-HT.…”
Section: Increased Extracellular Concentration Of 5-ht Enhances Centrmentioning
confidence: 99%
See 2 more Smart Citations
“…It was therefore concluded that fatiguing cycling exercise results in an inhibition, or disfacilitation, of the spinal motoneurons. Potential mechanisms for decreased excitability of the motoneuron pool resulting from fatiguing exercise include alterations in motoneuronal membrane potential (e.g., increased after-hyperpolarization (Matthews, 1999)), activation of extrasynaptic serotonin 1A receptors (D’Amico et al, 2017), and insufficient release, or depletion, of neurotransmitters (e.g., acetylcholine) resulting from repetitive activation.…”
Section: Changes In the Excitability Of The Corticospinal Pathway Durmentioning
confidence: 99%